1976
DOI: 10.1111/j.1365-2125.1976.tb04871.x
|View full text |Cite
|
Sign up to set email alerts
|

An Electroencephalographic Investigation of Short‐term Effects of Three Hypothalamic Hormones (Trh, Lh/Fsh‐rh, Gh‐rih) in Normal Subjects

Abstract: 1. Three hypothalamic regulatory hormones, thyrotrophin-releasing hormone (TRH), luteinizing hormone/follicle-stimulating hormone-releasing hormone (LH/FSH-RH) and growth hormone-release inhibiting hormone (GH-RIH) given intravenously had no effect on the electroencephalographic response known as the contingent negative variation (CNV) in normal subjects. 2 TRH was given as a 10 ml infusion of 600 ,ug over 8 min to six subjects. This produced subjective sensations and a rise in heart rate but no significant al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1976
1976
1990
1990

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In agreement with the present study, Miller et al (1974) found no significant change in CNV magnitude in 10 subjects after ACTH 4-10, although these authors state that "the CNV ... did tend to be somewhat more negative (P < 0.15) following ACTH 4-10 injections .... " A study of three hypothalamic polypeptides-thyrotrophin releasing hormone, luteinising hormone/follicle stimulating hormone releasing hormone, and growth hormone-release inhibiting hormone-in normal subjects revealed no effects on CNV magnitude (Ashton et al, 1976). Kastin et al (1971) noted large increases in EEG auditory evoked potentials after alpha MSH, a phenomenon not seen in the present study.…”
Section: Discussionmentioning
confidence: 87%
“…In agreement with the present study, Miller et al (1974) found no significant change in CNV magnitude in 10 subjects after ACTH 4-10, although these authors state that "the CNV ... did tend to be somewhat more negative (P < 0.15) following ACTH 4-10 injections .... " A study of three hypothalamic polypeptides-thyrotrophin releasing hormone, luteinising hormone/follicle stimulating hormone releasing hormone, and growth hormone-release inhibiting hormone-in normal subjects revealed no effects on CNV magnitude (Ashton et al, 1976). Kastin et al (1971) noted large increases in EEG auditory evoked potentials after alpha MSH, a phenomenon not seen in the present study.…”
Section: Discussionmentioning
confidence: 87%
“…In this respect, it could be valuable to extend the recording period of most pharmaco-EEG studies on hormones: the present re sults on night sleep might have benefited from a longer time schedule of recording. Also, the negative results reported by Ashton et al [1976] on the effect of hypothalamic hormones (TRH, LH, GH) on CNV could have been different if the recording had been pursued over more than 4 h following drug intake.…”
Section: Discussionmentioning
confidence: 98%
“…It has no effect on the contingent negative variation, a sensitive indicator of the brain activity which results from other agents such as diazepam and nicotine (Ashton et al, 1976).…”
mentioning
confidence: 99%